2011
DOI: 10.1016/j.ijid.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in leishmaniasis treatment

Abstract: About 1.5 million new cases of cutaneous leishmaniasis and 500,000 new cases of visceral leishmaniasis occur each year around the world. For over half a century, the clinical forms of the disease have been treated almost exclusively with pentavalent antimonial compounds. In this review, we describe the arsenal available for treating Leishmania infections, as well as recent advances from research on plants and synthetic compounds as source drugs for treating the disease. We also review some new drug-delivery sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
237
0
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(257 citation statements)
references
References 109 publications
1
237
0
19
Order By: Relevance
“…It is quite alarming to note that approximately 1.5 million of new cases of cutaneous leishmaniasis emerge every year while there is an outbreak of about 500 000 of new cases of visceral diseases in similar vein. Statistics have shown that cutaneous leishmaniasis is endemic over 70 countries of the World today (Tiumana et al, 2011). Comprehensive review of anti-leishmanial drugs discovered for the last decade projected quinazoline as highly promising in this regard (Sangshetti et al, 2015).…”
Section: Antileishmanial Activitymentioning
confidence: 99%
“…It is quite alarming to note that approximately 1.5 million of new cases of cutaneous leishmaniasis emerge every year while there is an outbreak of about 500 000 of new cases of visceral diseases in similar vein. Statistics have shown that cutaneous leishmaniasis is endemic over 70 countries of the World today (Tiumana et al, 2011). Comprehensive review of anti-leishmanial drugs discovered for the last decade projected quinazoline as highly promising in this regard (Sangshetti et al, 2015).…”
Section: Antileishmanial Activitymentioning
confidence: 99%
“…Other drugs available in the market face great challenges such as acquired resistance by certain common species, depleted immune capability in HIV co-infection patients and organs toxicities [2]. The unfavorable side effects and resistance together with the increasing number of patients intensified the demand for alternative remedies to curtail this disease [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The promastigotes are then transformed to amastigotes and then multiply, causing host cells to be burdened with parasites and thus becoming prone to lysis. The lysis will release amastigotes which then may infect other macrophages, thus ensuring their survival in the host [8,10]. The disease is characterized by a spectrum of clinical manifestations which are visceral leishmaniasis (VL) and cutaneous leishmaniasis (CL), and also rarer ones such as mucosal leishmaniasis (MCL) [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations